Financial Performance of New Private Banks with other Bank Groups in the Banking Industry - Ramachandran, A.; Kavitha, N. (Indian Journal of Finance, 2008)
Banking industry plays a vital role in rejuvenating and revamping the economic growth of a country. The banking sector is the major purveyor of money in an economy, hence the banker is the best ’cash flow’ manager of a country. During industrialization, finance was considered as the major input for achieving industrial growth. Banking industry is playing a role of a catalyst by providing financial assistance to various sectors of economy viz., agriculture, industry and service. The recent past has witnessed drastic changes in the Indian economy. When the economy is witnessing sea change, obviously the banking sector is bound to change in tandem.